The Escalation of Finance Literation and Simple Book-keeping Training for Small and Medium Enterprises (SMEs) at Desa Sulahan - Putri, Putu Galuh Gita Anindya; Putri, Dewa Ayu Putu Adhiya Garini; Permana, Gusi Putu Lestara (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The community service that will be carried out by our team is located in Sulahan Village, Susut District, Bangli Regency which consists of 9 traditional villages namely the traditional villages of Alis Bintang, Cekeng, Bungkuan, Lumbuan, Kikian, Kebon, Tanggahan Peken, Tanggahan Gunung, and Sulahan traditional village. Not a few people in Sulahan Village work as entrepreneurs, especially MSME entrepreneurs such as bamboo crafts, lolo, processed food and others. There are MSME business actors who are still starting business activities, but there are also business actors who have been doing business for a long time but their businesses have not been able to develop properly. Based on a survey conducted in the field, it was shown that the high level of business activity carried out by business actors has not been accompanied by an understanding of supporting factors in carrying out business activities such as simple bookkeeping so that business actors only focus on profits without paying attention to business supporting factors. Based on this illustration, the program orientation is to provide education and training to business actors, so that they are able to prepare their financial reports independently and responsibly. So that the capital capability of business actors is feasible to develop their business. The solution offered by the executor of community service is training in preparing financial reports using simple bookkeeping techniques. With the intent and purpose of providing this simple bookkeeping training it can assist business actors in managing their finances in a professional manner.